Surviving the lockdown and beyond - Toby C. Monsod; Orville Jose C. Solon; Maria Socorro Gochoco-Bautista; Emmanuel S. de Dios; Joseph J. Capuno; Ma. Joy Abrenica; Agustin L. Arcenas; Ma. Christina Epetia Epetia; Laarni C. Escresa; Karl Robert L. Jandoc; Aleli D. Kraft; Cielo Magno; et al. (University of the Philippines, School of Economics (UPSE), 2020)
Are new mayors more responsive to disasters than their reelected counterparts? The identification strategy is based on slim vote margin in which new and reelected mayors are found to be as if randomly assigned. We find that with greater storm exposure: new mayors spend more on health sector than reelected mayors. We don't find stable and statistically significant result in other sectors and in total municipal income or expenditure
Keywords: 330; COVID-19; Philippines